Evaluation The Effects of Extracts of Zataria, Carum and Geranium on Different Stages Haemonchus contortus (nematode) invitro and invivo condition - SH Hosseini; S Haghighi; B Meshgi (Institue of Medicinal Plants, ACECR, 2007)
Background: In Iran different species from Zataria, Carom and Geranium are present and in some areas are endemic. There is no report about effect of this herbal extracts on helminth parasites. Objective: This study aims at investigating the effect of three herbal extracts of Zataria, Carom and Geranium on different stages including egg, larvae and mature of Haemonchus contortus, parasitic nematode of sheep. Methods: After experimental infection of the lambs was determinated the number of egg per gram (EPG) of feces and its cultured. Evaluating the effect of the extracts breeding, a plant synthesis along with the control group were added to the feces samples separately and after placing the sample in the incubator for its culture and then examined light microscope to evaluate of hatching status. Furthermore, in order to evaluate the effect of extracts on larvae stage, three different volume of herbal extracts were added to the larvae and the percentage of lost larvae was counted through in different period (0, 5, 10, 15, 20, 30, 40 and 60 min). Infected lambs were fed by hand during their maintenance and a month after contamination the volume of 20 cm3 of each extract was fed to each lamb. Results: The results showed that three extracts of, Zataria, Carom and Geranium have the effect of 89.9%, 21.6% and 6.6% on egg stage of Haemonchus contortus, respectively. Besides, with direct contact of the larvae, the Zataria extract caused 95.7% 97.7% and 100% loss in volume of 0.01, 0.02 and 0.03 cm3 after 10 min and the extracts of Carom and Geranium caused 83.2%, 87.5%, 86% and 65.8%, 77.6% and 78.5% respectively. The field condition and necropsy results showed the lack of extracts effects on the adult stage of Haemonchus contortus.